A plan to present the Greeks abroad through the Project method - Tsantali, Calliope; Nikolidakis, Symeon (International Journal of Language, Translation and Intercultural Communication, 2015)
The present paper is concerned with students’ sensitization about the Greeks abroad who are introduced through the Project method to reinforce national awareness, especially during an economic crisis period when the economic choices followed by Greece are disapproved. The dynamics of the Greek communities abroad towards the economic and cultural development of the countries of reception and the concurrent enhancement of their bonds with Greece are pinpointed. The contact between the Greek native students and the offspring of the Greeks abroad is pursued towards an exchange of viewpoints, considerations and information about issues of politics, economy and culture. As a result, they all have a sense of solidarity in an expanded Greece encompassing the Greeks’ communities abroad. History and the History of Civilization are utilized to present this topic through the Project method. This way, emphasis is placed on migration, national identity, solidarity and the dynamics developed by the population mobility in the globalized societies. The Project method forms the suitable ground to cultivate and develop such objectives. Thus, students will formulate perceptions and examine the specific issues from a different perspective. A combination of theoretical issues of nationalism with a post-modern narration about nationalism in the globalized societies is conducted, where the national identity is reinforced and the citizens’ role in the globalized societies is not overlooked.